2022
DOI: 10.1001/jamaneurol.2022.0154
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Assessment of Olfactory Tissue Degeneration and Microvasculopathy in Patients With COVID-19

Abstract: IMPORTANCELoss of smell is an early and common presentation of COVID-19 infection.Although it has been speculated that viral infection of olfactory neurons may be the culprit, it is unclear whether viral infection causes injuries in the olfactory bulb region.OBJECTIVE To characterize the olfactory pathology associated with COVID-19 infection in a postmortem study. DESIGN, SETTING, AND PARTICIPANTSThis multicenter postmortem cohort study was conducted from April 7, 2020, to September 11, 2021. Deceased patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…This is important for two reasons. First, the severity of microvascular endotheliopathy seen in olfactory tissue in acute COVID-19 correlates with the extent of olfactory axonal damage ( 104 ). Second, even if non-neuronal cells are the main targets of the virus in the olfactory mucosa ( 105 ), these cells could be a source of persistent viral RNA in PASC.…”
Section: Sars-cov-2 Reservoirs May Underlie Endotheliopathy In Pascmentioning
confidence: 99%
“…This is important for two reasons. First, the severity of microvascular endotheliopathy seen in olfactory tissue in acute COVID-19 correlates with the extent of olfactory axonal damage ( 104 ). Second, even if non-neuronal cells are the main targets of the virus in the olfactory mucosa ( 105 ), these cells could be a source of persistent viral RNA in PASC.…”
Section: Sars-cov-2 Reservoirs May Underlie Endotheliopathy In Pascmentioning
confidence: 99%
“…Since it was reported that surgically-induced disruption of olfactory bulb function through olfactory bulbectomy (OBX) resulted in a decrease in ChAT positive cells in the MS 43 , the decrease in ChAT positive cells and disruption of the CAP in the S1 mouse could be due to olfactory bulb dysfunction. Thus, severe damage to the olfactory bulb due to SARS-CoV-2 infecting the olfactory system 44,45 could be the main cause of CAP disruption in COVID-19. However, the olfactory bulb damage in the S1 mouse was thought to be due to the calcium elevating activity of S1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection of the OE results in an inflammatory environment. A recent report by Ho et al provided evidence for the degeneration of olfactory axon injury microvasculopathy in the post-mortem samples, and this indicates a local inflammation in the micro-vessels [92]. It is accompanied by the infiltration of the innate immune cells, as evidenced by co-staining for IBA, a myeloid marker, and the N protein of SARS-CoV-2 [66].…”
Section: Cell-autonomous Mechanismmentioning
confidence: 93%